2008
DOI: 10.1024/0036-7281.150.12.599
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia recovery quality after racemic ketamine or S-ketamine administration to male cats undergoing neutering surgery

Abstract: Postoperative anaesthesia recovery and analgesia qualities were compared in cats anaesthetised with racemic ketamine (RS-ket) or S-ketamine (S-ket) undergoing orchiectomy. Twenty client-owned male cats received medetomidine (0.03 mg/kg) and S-ket (6 mg/kg; n = 10) or RS-ket (10 mg/kg; n = 10), all intramuscularly. After routine orchiectomy, animals received atipamezole (0.15 mg/kg) intramuscularly. Thirty and 60 min after atipamezole administration, one observer unaware of the treatment identity evaluated anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 0 publications
2
19
0
3
Order By: Relevance
“…50 Some studies show that ketamine S(+) presented a better clearance and, consequently, lower effective period and a faster anesthetic recovery. 51,52 In a report comparing equal doses of racemic and S(+) ketamine associated with midazolam in common marmosets did not see any difference as to induction and recovery times. 8 However, they observed that animals that received the racemic ketamine presented a longer period of immobilization.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…50 Some studies show that ketamine S(+) presented a better clearance and, consequently, lower effective period and a faster anesthetic recovery. 51,52 In a report comparing equal doses of racemic and S(+) ketamine associated with midazolam in common marmosets did not see any difference as to induction and recovery times. 8 However, they observed that animals that received the racemic ketamine presented a longer period of immobilization.…”
Section: Discussionmentioning
confidence: 97%
“…Cats treated with dexmedetomidine presented a longer recovery period, but with better quality, smoother, and with better movement control . Some studies show that ketamine S(+) presented a better clearance and, consequently, lower effective period and a faster anesthetic recovery …”
Section: Discussionmentioning
confidence: 99%
“…Based on studies in rats, mice and man it has been suggested that, in comparison to the racemate, the dose of S-ketamine should be reduced by 50-70% for anaesthetic use (Ryder et al 1978;White et al 1985). In recent years S-ketamine has been introduced in veterinary practice and its use has been reported in horses, dogs, cats and laboratory animals (Muir & Hubbell 1988;Larenza et al 2008aLarenza et al , 2009Rossetti et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Em medicina, é muito utilizada como medicação pré-anestésica pela via intranasal, com boa eficácia e sem efeitos adversos para sedação em crianças (Diaz 1997). A cetamina S+ é o enantiômero levógiro da cetamina racêmica e apresenta maior afinidade a receptores NMDA, maior potência analgésica e menos efeitos adversos com menores doses quando comparada a cetamina racêmica (Duque et al 2008, Larenza et al 2008a, 2008b. Pelas características peculiares da cetamina S+, optou-se, no presente estudo, pela utilização da menor dose deste fármaco (20mg/kg) preconizada para anestesia de pombos.…”
Section: Resultsunclassified
“…Esta discrepância entre resultados pode ser decorrente da grande variedade intra e interespécies de pássaros (Samour et al 1984), considerando que diferentes famílias de pássaros foram avaliadas nos outros estudos, o que pode resultar em particularidades na biotransformação dos fármacos e na ação farmaco-lógica destes. Outra diferença importante é que a dose da cetamina S+ deste estudo (20mg/kg) foi metade da dose utilizada em periquitos (40 mg/kg), o que também poderia justificar a menor duração de ação nos pombos, apesar de alguns autores afirmarem que a cetamina S+, por apresentar maior efeito analgésico e maior potência, pode ter sua dose reduzida como o observado para gatos, cães e pôneis (Duque et al 2008, Larenza et al 2008a, 2008b.…”
Section: Discussionunclassified